Obstetric History and Likelihood of Preterm Birth of Twins - Easter, Sarah Rae; Little, Sarah E.; Robinson, Julian N.; Mendez-Figueroa, Hector; Chauhan, Suneet P. (American Journal of Perinatology, 2018)
Objective The objective of this study was to investigate the relationship between preterm birth in a prior pregnancy and preterm birth in a twin pregnancy.Study Design We performed a secondary analysis of a randomized controlled trial evaluating 17-α-hydroxyprogesterone caproate in twins. Women were classified as nulliparous, multiparous with a prior term birth, or multiparous with a prior preterm birth. We used logistic regression to examine the odds of spontaneous preterm birth of twins before 35 weeks according to past obstetric history.Results Of the 653 women analyzed, 294 were nulliparas, 310 had a prior term birth, and 49 had a prior preterm birth. Prior preterm birth increased the likelihood of spontaneous delivery before 35 weeks (adjusted odds ratio [aOR]: 2.44, 95% confidence interval [CI]: 1.28–4.66), whereas prior term delivery decreased these odds (aOR: 0.55, 95% CI: 0.38–0.78) in the current twin pregnancy compared with the nulliparous reference group. This translated into a lower odds of composite neonatal morbidity (aOR: 0.38, 95% CI: 0.27–0.53) for women with a prior term delivery.Conclusion For women carrying twins, a history of preterm birth increases the odds of spontaneous preterm birth, whereas a prior term birth decreases odds of spontaneous preterm birth and neonatal morbidity for the current twin pregnancy. These results offer risk stratification and reassurance for clinicians.
Keywords: twins; preterm birth; multiple pregnancy; neonatal morbidity